Service-Learning with Young Students: Validating the Introduction of Service-Learning in Pre-service Teacher Education - Arrington, Nancy McBride (International Journal of Research on Service-Learning in Teacher Education, 2015)
Founded on experience as a practitioner and teacher action-researcher in an elementary school setting, the author shares this study as a validation for introducing the methodology of service-learning in teacher preparation programs. Multiple methods were used in this action research to analyze the effects of participating in a service-learning experience on the self-efficacy for self-regulated learning of a class of third-grade music students as they participated in an intergenerational projectsharing music and writing with residents in a local nursing home. The quantitative data included the results from the Childrens Self-Efficacy Scale (Bandura, 2006) and progress rating scales administered by the teacher-researcher. These data were analyzed using independent samples t-tests and regression analyses. The qualitative data included observation and field notes, students reflective journals, student and teacher interviews, classroom artifacts, and informal discussions with the homeroom teacher. Emergent coding of these qualitative data revealed recurring themes, and the results supported the findings of the quantitative analyses. The analyses revealed that the students who participated in the service-learning experience improved their self-efficacy ratings for self-regulated learning significantly more than the students who did not participate in the project.